Knowledge level, Attitude, and Behavior Regarding Toxoplasmosis Among Medical Students of Universitas Sumatera Utara - Maurin, Ajeng Putri; Darlan, Dewi Masyithah (Universitas Muhammadiyah Sumatera Utara, 2021)
Toxoplasmosis is an infection caused by a single-celled parasite calledToxoplasma gondii.Toxoplasma gondiican infect almost all warm-blooded animals and humans. Toxoplasmosis is still prevalent worldwide, particularly in tropical countries including Indonesia. Various factors contribute to the prevalence, involving a lack of knowledge, attitude, and behaviour towards toxoplasmosis. This study was aimed to determine knowledge level, attitude, and behaviour on toxoplasmosis among medical students of Universitas Sumatera Utara. This was an analytical study with across-sectionaldesign. Data collection was conducted using a questionnaire instrument. The consecutive sampling method was used to enroll the subjects from medical students of Universitas Sumatera Utara class year of 2017-2020 who met the inclusion and exclution criteria. The results showed that, based on gender, the p-value of the knowledge, attitude, and behaviour were 0.72, 0.02, and 0.285, respectively. Based on the age, the p-value of the knowledge, attitude, and behaviour were 0.013, 0.141, and 0.405. According to the class year, the p-value of the knowledge, attitude, and behaviour were 0,006, 0,138, and 0,919. This results indicated a significant difference in attitude (based on gender) and knowledge level (based on age and the class year).